2023
DOI: 10.1007/s40820-023-01155-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Gemini Surfactant-Assisted Blade Coating Enables Large-Area Carbon-Based Perovskite Solar Modules with Record Performance

Abstract: Carbon-based perovskite solar cells show great potential owing to their low-cost production and superior stability in ambient air. However, scaling up to high-efficiency carbon-based solar modules hinges on reliable deposition of uniform defect-free perovskite films over large areas, which is an unsettled but urgent issue. In this work, a long-chain gemini surfactant is introduced into perovskite precursor ink to enforce self-assembly into a network structure, considerably enhancing the coverage and smoothness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…S7b (ESI†), the critical micellar concentration (CMC) is determined to be 0.3 mg mL −1 and micelles are expected to form in the bulk solution. 29 On one hand, oleate anion can orient hydrophilic carboxyl groups towards the aqueous phase and hydrophobic long alkyl chains towards the air phase. These molecules build a compact homogeneous adsorption layer on the surface, effectively reducing the surface tension of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…S7b (ESI†), the critical micellar concentration (CMC) is determined to be 0.3 mg mL −1 and micelles are expected to form in the bulk solution. 29 On one hand, oleate anion can orient hydrophilic carboxyl groups towards the aqueous phase and hydrophobic long alkyl chains towards the air phase. These molecules build a compact homogeneous adsorption layer on the surface, effectively reducing the surface tension of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…[94] Ren et al also reported a P3HT:graphene composite HTL large-area-based PSC with a 15.46% PCE achieved after adding 1,2-distearoyl-snglycero-3-phosphocholine (DSPC) to perovskite film to ensure a uniform blade coating. [95] Other Inorganic Additives: Tris(2-(1H-pyrazol-1-yl)pyridine) cobalt(II) di[bis(trifluoromethane)sulfonimide] (Co(II)-TFSI) was reported by Jung and co-workers as a dopant for P3HT HTL. [73] Cobalt introduction enhanced the conductivity and charge extraction leading to a downward shift in energy levels achieving a considerable PCE of 16.28% with better air stability than the Li-doped P3HT devices.…”
Section: Inorganic Additivesmentioning
confidence: 99%
“…[131] Further improvements were reported by Ren et al's previously mentioned work with a 50 cm 2 fully printed module achieving a high 17.05% PCE. [95]…”
Section: P3ht In Psc Modulesmentioning
confidence: 99%
“…Currently, there is an urgent need to develop high-performance devices that are commercially viable, where the counter electrode (CE) plays an important role in determining the performance, cost, and even stability of PSCs . Carbon-based CEs are a promising alternative to metal electrodes (i.e., Au and Ag) on the road to the commercialization of PSCs owing to their suitable work functions, good chemical stability, scalable large-area fabrication, and ultralow cost. In traditional planar PSCs, hole transport layers (HTLs) are commonly used to accelerate hole carriers transport, but the traditional organic HTLs (i.e., Spiro-OMeTAD) also face the problem of instability and high costs. , To address the issue, the bipolar charge transport characteristics of the perovskite permit the diffusion of hole carriers to the CE and make the HTL-free configuration rational . Carbon-based CEs in HTL-free PSCs thus possess promising potential for commercialization. …”
mentioning
confidence: 99%